Nutritional composition, phenolic compounds, and sensory evaluation of osmosonicated orange peel snacks impregnated with plant extracts - Botta Arias, Vanessa Luisa (2025)
The demand for increasingly healthier food products requires challenges from food processors, to produce foods with better sensory properties, fortified with micronutrients and bioactive compounds of natural origin. This study addresses a novel formulation of osmosonicated orange peel snacks, impregnated with plant extracts during osmodehydration. Extracts of purple corn, camu-camu, lucuma, carob and prickly pear were used as hypertonic solution. Sucrose solution was used as control. Snacks exhibits adequate moisture values, important content of fibre and slightly reduction of proteins. Snacks with plant extracts had less content of carbohydrates than control. A preservation and/or reduced loss of bioactives compounds of the snacks was observed, being the ferulic acid, the main phenolic. The antioxidant activity was enhanced with the use of osmosonication and heat dehydration. Color changes were observed according to the different plant extracts used. The sensory quality exhibits a good acceptability for all snacks, mainly the snack impregned with lucuma extract.